2016
DOI: 10.1039/c6py00745g
|View full text |Cite
|
Sign up to set email alerts
|

A practical ethylene polymerization for vinyl-polyethylenes: synthesis, characterization and catalytic behavior of α,α′-bisimino-2,3:5,6-bis(pentamethylene)pyridyliron chlorides

Abstract: A series of α,α′-bis(arylimino)-2,3:5,6-bis(pentamethylene)pyridyliron chlorides exhibits high activities toward ethylene polymerization, yielding highly linear vinyl-polyethylenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
105
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 67 publications
(118 citation statements)
references
References 65 publications
12
105
1
Order By: Relevance
“…On the other hand, after one hour the activity had only reduced to 2.59 × 10 6 g PE (mol of Co) −1 h −1 ] indicating that deactivation become more gradual over more extended run times. These collective findings indicate that the active species was quickly formed using MMAO without any significant induction period and then experienced a rapid deactivation process over the first thirty minutes before assuming a more constant level of performance . Meanwhile, the molecular weight increased from 155.9 kg mol −1 after 5 min to 206.5 kg mol −1 at the one hour mark in line with increased chain propagation (entries 2, 11–14, Table ).…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…On the other hand, after one hour the activity had only reduced to 2.59 × 10 6 g PE (mol of Co) −1 h −1 ] indicating that deactivation become more gradual over more extended run times. These collective findings indicate that the active species was quickly formed using MMAO without any significant induction period and then experienced a rapid deactivation process over the first thirty minutes before assuming a more constant level of performance . Meanwhile, the molecular weight increased from 155.9 kg mol −1 after 5 min to 206.5 kg mol −1 at the one hour mark in line with increased chain propagation (entries 2, 11–14, Table ).…”
Section: Resultsmentioning
confidence: 87%
“…The highest activity of 10.1 × 10 6 g PE (mol of Co) −1 h −1 was observed after 5 minutes (entry 10, Table ) which by the 30 min mark had dropped by only 19% [7.19 × 10 6 g PE (mol of Co) −1 h −1 ]. Notably, even after 1 hr the activity had only declined to 3.94 × 10 6 g PE (mol of Co) −1 h −1 ] (entry 13, Table ), which underlined the remarkable thermal stability of the active species at this temperature . The GPC traces showed that longer reactions were accompanied by increases in M w from 14.4 to 21.2 kg mol −1 (Figure ).…”
Section: Resultsmentioning
confidence: 92%
“…As an alternative strategy in bis(imino)pyridine ligand design, our group has recently explored the fusion of carbocycles to the central pyridine unit in (Figure 1) as a means to form well-defined Fe-/Co-based complexes bearing singly [22][23][24][25][26][27][28][29][30] and doubly fused derivatives (e.g., B, C, D, and E in Figure 1) [31][32][33][34][35][36][37][38]. Indeed, the fused ring size has been shown to be pivotal to the catalytic activity and polymeric properties [6,[36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the fused ring size has been shown to be pivotal to the catalytic activity and polymeric properties [6,[36][37][38]. Of particular note, iron-containing B [31], C [32], and D [36] can produce strictly linear polyethylenes with a wide range of molecular weights, end-group types, and activities (up to 10 7 g(PE) mol -1 (Fe) h -1 ) [6,36]. For example, six-membered B produced the lowest molecular weight polymer (8 kg mol -1 ) [31], while seven-and eight-membered C and D showed a predilection towards higher molecular weight vinyl-polyethylenes (up to 188 kg mol -1 ) [32,36].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, both the 1 H NMR and 13 C NMR spectra showed that the PE samples were strictly linear. 14,23 As a general comment, these highly linear, low molecular vinyl-polyethylenes are likely to be of high demand as new comonomers for long-chain branched polymers and coating materials. Hence, a coordination-insertion mechanism allows chain propagation and β-hydrogen elimination facilitates chain termination to afford these vinyl-terminated linear polyethylenes (Scheme 3).…”
Section: 13mentioning
confidence: 99%